2010
DOI: 10.5539/ass.v6n8p19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Comprehension Strategy Instruction on EFL Learners’ Reading Comprehension

Abstract: The purpose of this study is to investigate the effect of Collaborative Strategic Reading (CSR) on Taiwanese university students' reading comprehension with reference to specific types of reading comprehension questions. The participants were 110 students from two intact classes who had low-intermediate to intermediate level of English. This study adopted a pre-test and post-test design with a control group. The data mainly came from statistical results of One-Way ANOVA, but would be triangulated by multiple d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
4
31
0
1
Order By: Relevance
“…Among various reading' strategy approaches, Collaborative Strategic Reading (CSR) rendered by Klingner and Vaughn (1998) has been widely used in different research studies. Many studies on CSR (Klingner, 1998;Standish, 2005;Fan, 2010;Ziyaeemehr, 2012;Novita, 2012;Karabuga, 2012) have shown that CSR has an effective impact on reading comprehension of EFL and ESL students .CSR provides the opportunity for readers to apply most of the strategies needed for the reading skill. Through the collaborative approach emphasized with CSR, student learning is supported by both teachers and peers (Vaghaun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among various reading' strategy approaches, Collaborative Strategic Reading (CSR) rendered by Klingner and Vaughn (1998) has been widely used in different research studies. Many studies on CSR (Klingner, 1998;Standish, 2005;Fan, 2010;Ziyaeemehr, 2012;Novita, 2012;Karabuga, 2012) have shown that CSR has an effective impact on reading comprehension of EFL and ESL students .CSR provides the opportunity for readers to apply most of the strategies needed for the reading skill. Through the collaborative approach emphasized with CSR, student learning is supported by both teachers and peers (Vaghaun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Highly motivated readers are said to be strategic and employ deep conceptual strategies to comprehend (Wigfield, Guthrie, Perencevich, Taboada, Lutz Klauda, McRae & Barbosa, 2008: 432). Fan (2010) found that the use of collaborative strategies had a positive impact on students' reading comprehension and learning motivation. Various means of motivating students have been advocated, with learner autonomy and student choices being the most significant.…”
Section: Affective Factors In Readingmentioning
confidence: 99%
“…Many researchers have investigated Language Learning Strategies (LLS) 1 and Strategy Instruction (SI) 2 using mixed methods research, or they may have used pragmatism implicitly as a theoretical approach to guide the design and implementation of their studies (e.g., Bai, 2015;Fan 2010;Hong-Nam and Leavell 2011). However, using pragmatism explicitly in shaping LLS and SI research can provide the backbone of the research and a more complete understanding of the results during data integration because it allows abductive reflection on the knowledge-reasoning phase by moving back and forth through induction and deduction (Morgan 2007).…”
Section: Introductionmentioning
confidence: 99%